Resisting the Colonial Narrative of the Legend of Paoay Lake: Recounting a Story of Biag nga Agnanayon/Life Eternal in an Ilokano Barrio in Paoay, Ilocos Norte - Leonardo D. Tejano (Integrated Journal for Research in Arts and Humanities, 2022)
This study embarked on the question: why would I allow a story full of colonial elements to become my legend or the story of the space of my existence? Thus, in this study, the author attempted to recount alternative stories about Paoay Lake, specifically from the experiences of people living in the Barrio Suba, of the Municipality of Paoay, province of Ilocos Norte, Philippines. Analyzing from the lens of two emerging concepts in Ilokano and Amianan Studies, pakasaritaan and purok ti isip, as well as using Ilokano data collection methods, this study was able to recount two stories of rituals, the ritual of digos, (ritual of naming while bathing in the dakkel a danum or Paoay Lake), and the ritual of gulgol, or the cleansing ceremony. Towards the conclusion of this paper, the author will lay out the alternative lens of the narrative about Paoay, which in this paper he has tentatively viewed as a manifestation of the Ilokano belief of Biag nga Agnanayon or Life Eternal as both rituals require the continuous passing of knowledge, the keeping of records, and the telling of stories; and as stories carry memories of life, as long as this is passed, kept, and told, it can be said that life is sustained, or life eternal. This study therefore suggests a turnaround from the colonial narrative of the Legend of Paoay Lake but to focus the storytelling now on the experiences of the people and on the writing of stories that will allow them to connect, reflect, react, and own the stories.